2010
DOI: 10.1142/s0192415x10008263
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Oxidant Capacity of Root of Scutellaria baicalensis Georgi, in Comparison with Roots of Polygonum multiflorum Thunb and Panax ginseng CA Meyer

Abstract: In Chinese communities, regular consumption of Chinese-medicated diets (CMD) (usually in the form of soup) is a traditional practice to promote health and prevent disease development. The overall improvement of health conditions is believed to be correlated with the anti-oxidant potentials of these herbs. Huangqin, roots of Scutellaria baicalensis Georgi (Lamiaceae), is one of the herbs commonly used in CMD. In this study, the anti-oxidant capacities of Huangqin extracts (water, ethanol and ether extracts) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 27 publications
1
33
1
Order By: Relevance
“…In traditional Chinese medicine (TCM), it is believed that food and medicine stem from the same origin but with different uses and applications (Chan et al, 2010). Therefore, it is common for Chinese people to incorporate different medicinal herbs into their diet to produce various "healthy" food recipes in order to achieve better taste, more attractive appearance and improved texture of the food and most importantly to improve health.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional Chinese medicine (TCM), it is believed that food and medicine stem from the same origin but with different uses and applications (Chan et al, 2010). Therefore, it is common for Chinese people to incorporate different medicinal herbs into their diet to produce various "healthy" food recipes in order to achieve better taste, more attractive appearance and improved texture of the food and most importantly to improve health.…”
Section: Introductionmentioning
confidence: 99%
“…Various natural compounds are effective in suppressing AD like pathology through their properties as anti-oxidants (Dos Santos-Neto et al, 2006;Frank and Gupta, 2005). Our team has even shown that Panax ginseng has a high content of anti-oxidants (Chan et al, 2010a;Chan et 8 al., 2008). Panax ginseng's effect on cognitive performances were evaluated in consecutive AD patients (Lee et al, 2008).…”
Section: Improves Cognition In Alzheimer's Disease (Ad)mentioning
confidence: 93%
“…In traditional Chinese medicine (TCM), it is believed that food and medicine come from the same origin but with different uses and applications (Chan et al, 2010a). Therefore, it is common 4 for Chinese people to incorporate different TCM herbs into their diet to produce various "healthy" food recipes so as to achieve better taste, more attractive appearance and improved texture of the food and most importantly to improve health .…”
Section: Introductionmentioning
confidence: 99%
“…MCF-7 cells were seeded in 96-well microtiter plates at a density of 1x10 4 cells/well in 200 µl medium; the medium was replaced the following morning with 200 µl of fresh complete medium containing PME of different final concentrations. Cells were treated with PME for different times according to the experimental requirement, using DMSO as vehicle at a maximum concentration of 0.1%.…”
Section: Materials Pm Was Obtained From the Harbin Branch Of Pekingmentioning
confidence: 99%
“…Clinically, it has been utilized in the treatment of poliosis, hemopenia, inflammation, bacterial infections, hyperlipidemia, coronary heart disease, neurosis and other diseases commonly associated with aging (2,3). The medicinal effects of PM in the improvement of health conditions are possibly mediated by the antioxidant capacity of this herb (4). The genus PM is the source of a wide range of phenolic compounds, flavonoids, anthraquinones, stilbenes and tannins (5,6).…”
Section: Introductionmentioning
confidence: 99%